2018
DOI: 10.1097/md.0000000000013638
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma with crystal-storing histiocytosis, crystalline podocytopathy, and light chain proximal tubulopathy, revealed by retinal abnormalities

Abstract: Rationale:Crystal sorting histiocytosis (CSH) is a rare disorder that is morphologically characterized by the accumulation of monoclonal immunoglobulin crystals, predominantly of a kappa light chain type, within lysosomes of macrophages. CSH may result in a variety of clinical manifestations depending on the involved organs. In this case report, we aim to describe a patient with ophthalmic manifestations which lead to the diagnosis of multiple myeloma with crystal-storing histiocytosis, crystalline podocytopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
1
14
0
2
Order By: Relevance
“…This entity shows predominantly lambda light chain restriction [12]. Similar cases have already been described, some of which already fulfilled the criteria for MM or in which Fanconi syndrome was present [27,28]. FSGS reported in our case is a rare renal disorder in PCD.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This entity shows predominantly lambda light chain restriction [12]. Similar cases have already been described, some of which already fulfilled the criteria for MM or in which Fanconi syndrome was present [27,28]. FSGS reported in our case is a rare renal disorder in PCD.…”
Section: Resultssupporting
confidence: 84%
“…Although considered secondary, clinical symptoms of FSGS with underlying PCD may vary: Our patient showed proteinuria in the sub-nephrotic range without edema or hypalbuminemia. In contrast, other cases have been reported in which a full nephrotic syndrome was evident with pronounced proteinuria, edema, and hypalbuminemia [ 28 31 ]. In summary, the clinical picture of FSGS associated with PCD shows a wide range from only moderate proteinuria to full nephrotic syndrome, which should always be taken into account in diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…This prompted us to consider that collapsing FSGS manifestations were caused by the paraproteinemia itself, as no other causative factors were involved. Some studies have reported ultrastructural examination in favor of crystals coming from the urinary space after backflowing from the tubules because of proximal tubule obstruction by apoptotic epithelial cells 13 . Monoclonal proteins could be also endocytosed by podocytes and crystallize inside lysosomes, causing podocyte dysfunction due to accumulation of light chains.…”
Section: Discussionmentioning
confidence: 99%
“…CSH was diffuse and involved kidney (n = 2), bone marrow and spleen (n = 2), mesenteric panniculitis (n = 1), and lung (n = 1). Three patients had a MM [2,3,13] two a lymphoplasmacytic lymphoma [5,6] and one monoclonal gammopathy [7]. Light chain was always kappa (IgG [3], IgA [1], IgM [1] or LC only [1]).…”
Section: Resultsmentioning
confidence: 98%